(untitled) (Indian Journal of Animal Production and Management, 2024)
Sheep is one of the important livestock species which make a valuable contribution to the livelihood of the economically weaker sections of the society by providing income and nutritional security. Moringa oleifera is one of the potential tree forages which can be used as livestock feed due to its faster growth and higher nutritional attributes. The present study was conducted on 18 post weaned Nellore lambs of 3 months old having similar body weights, divided into three groups with 6 lambs in each group for a period of 90 days to study the effect of Moringa oleifera leaf meal (MOLM) as a protein supplement on growth performance and to evaluate the cost economics. T0, T1 and T2 are the experimental diets having MOLM at 0,15 and 30 per cent conventional protein replacement levels. The cost of feed per kg body weight gain in growing Nellore lambs fed with experimental diets was Rs.131.34, 111.15 and 105.44, respectively for T0, T1 and T2 diets. The total cost and cost of production per one kg of meat was lower in T1 and T2 group lambs which received concentrate mixture containing MOLM than control group lambs. Hence, it is recommended that MOLM can be a cheaper substitute for conventional protein supplements up to 30% level in the diets of growing Nellore lambs.